Tingkat Pengetahuan Dan Sikap Mahasiswa Kebidanan Dengan Anemia Di Stikes Akbidyo - Juliana Dwi Rahmawati; Sylvi Wafda Nur Amellia; Era Revika; Ari Andriyani (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: The prevalence of anemia in women in Indonesia is 27.2% of students, including the group vulnerable to anemia with the highest prevalence in young women aged 15-24 years. It was found that 8 out of 10 students do not have good knowledgeand attitudes, this is one of the factors that causes it to occur. anemia. This research aims to determine the relationship between knowledge and attitudes of midwifery students and anemia at STIKes Akbidyo.Research Method: This type of research uses quantitative analytical methods, with a cross-sectional approach. The population of this study were all midwifery students. Sampling used probability sampling techniques with a simple random sampling Tingkat Pengetahuan dan Sikap Mahasiswa Kebidanan dengan Anemia di STIKes Akbidyo approach. The data collection tool uses a g-form questionnaire with a Guttman and Likert scale and hemoglobin level values use easy touch GCHb. Meanwhile, the statistical test technique uses the Chi-Square test.Research Results: The hemoglobin levels of respondents who experienced anemia were 37.1%. The research results showed that the relationship between sufficient knowledge about anemia was 85.2% and the relationship between adequate attitudes about anemia was 62.9%. This shows that there is no significant relationship between knowledge and anemia of STIKes Akbidyo midwifery students with p-Value results of 0.811 > 0.05 and there is a significant relationship between attitudes and anemia of STIKes Akbidyo midwifery students with p-Value results of 0.022 > 0.05.Conclusion: The conclusion of this research is that the relationship between the level of knowledge and attitudes of midwifery students and anemia is said to be quite good regarding anemia at STIKes Akbidyo.Keywords: Knowledge, Attitude, Anemia